The Nawa Gapura Marga Raja Gate as a Representation of the Cirebon Islamic Monarchy in Indonesia during the 17th Century - Kartasudjana, Tata; Abdillah, Fadhly (JOMANTARA, 2023)
Cirebon's early manuscripts, specifically Prince Wangsakerta's Pustaka Rajyarajya I Bhumi Nusantara, the Kingdom of Cirebon begins to expand its realm as Islam starts to flourish in Cirebon. It was reported that the Kings occupied a structure in the shape of a gate. In Cirebon, the kings were to take part in "Gotrasawala" events that the Cirebon Kingdom was hosting. This is an article demonstrates that, in addition to serving as a gateway and fortress, this structure It also served as a stronghold, with a design that symbolizes the mixture of Islamic, Hindu, Buddhist, and Chinese civilizations. It is based on legends, oral histories, and information from Cirebon's culture and historian. In contrast to the history presented in the The families and descendants of the kings or leaders of the Cirebon Sultanate have provided more detailed supporting narratives to keepers, cultural heritage organizations, as well as culturalists.The continuity learned from interviews with the Cirebon area's source population, and Kasepuhan Palace in particular, was attempted by a detailed investigation using the Caretakers' oral history approaches The Kasepuhan Elders Palace family, historians, and culturalists. This page also coversthe type of Nawa Gapura Marga Raja, a historic gate that has influenced the growth of the Cirebon Kingdom in West Java's northern monitoring area since the 17th century.